ANTI-TUMOUR PROPERTIES OF ALOE VERA ETHANOLIC EXTRACT: EFFECTS ON DALTON'S ASCITIC LYMPHOMA IN SWISS ALBINO MICE - Anish Raj; Kokkula Pavan Kumar; Jayapal Reddy Gangadi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
With cancer remaining a critical worldwide health concern and conventional treatments often leading to adverse effects, this research examined how ethanolic extract derived from Aloe vera impacts Dalton's Ascitic Lymphoma (DAL) in Swiss albino mice. The study involved intraperitoneal injection of DAL cells (1×10⁶ cells/mouse) followed by Aloe vera extract administration at 100 mg/kg and 200 mg/kg doses over 14 days, using 5-fluorouracil (5-FU, 20 mg/kg) as a reference standard. The evaluation included measurements of tumour volume, weight changes, survival duration, blood parameters, and antioxidant activity. Results showed that Aloe vera's ethanolic extract significantly decreased tumour size and extended survival time proportional to dosage. Notably, the 200 mg/kg dose resulted in a 71.45% longer lifespan compared to untreated subjects. Blood parameters, including red blood cells, haemoglobin, and white blood cell counts, showed normalization in treated groups. The extract exhibited substantial antioxidant properties in both laboratory and living system tests, including DPPH, ABTS, superoxide radical scavenging, and nitric oxide scavenging activities. Furthermore, it enhanced antioxidant enzyme levels (SOD, CAT, GPx) within living systems. Tissue examination through histopathology confirmed these findings, revealing improved cellular structure in treated subjects. These outcomes indicate that Aloe vera demonstrates promising cancer-fighting and antioxidant capabilities, potentially due to its active plant compounds, suggesting the need for further research into its therapeutic potential in cancer treatment.